PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE TINJAUAN ALA PERMAINAN HOLLYWOOD SQUARES UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN KOLOID DI KELAS XI IPA SMA NEGERI 14 PEKANBARU - Darni, Satri; Haryati, Sri; ', Rasmiwetti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research aimed to increase student achievement by application of active learning strategies types reviews style game Hollywood Squares on learning topic of Colloid in XI IPA SMA N 14 Pekanbaru. This is an experimental research with randomized control group pretest-posttest design. Subject of this research are XI IPA 1 as the experimental class, XI IPA 3 as the control class which were determined randomly after conducting normality and homogeneity test. The experimental group was treated with the application of active learning strategies types reviews style game Hollywood Squares while the control group without the application active learning strategies types reviews style game Hollywood Squares. The data analysis to test the hypothesis was using t-test right side. Based on the data analysis, it is obtaine tcount = 2,39 and ttable = 1,67 with α=0,05, dk=59. tcount > ttable is 2,39 > 1,67, It’s mean that the application of active learning strategies types reviews style game Hollywood Squares can improve students achievement on the subject of colloid in XI IPA SMA Negeri 14 Pekanbaru. The raising student achievement category in the experimental class including a high score by normalized gain of 0,79.Keywords: active learning strategies types reviews style game Hollywood Squares, learning achievement